1994
DOI: 10.2527/1994.7271849x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and carcass quality of prolific crossbred lambs fed silage with fish meal or different amounts of concentrate1

Abstract: Sixty Romanov x Dorset (RVDP) and sixty Romanov x Suffolk (RVSU) male lambs were used in a 2 x 5 factorial arrangement of treatments including two breed crosses and five diets to determine the effect of breed crosses on performance and to compare growth and carcass characteristics of lambs. Diets consisted of an all-silage diet, silage supplemented with 100 g of fish meal.animal-1.d-1, or silage supplemented daily with concentrate at either 200 g or 400 g per animal, or ad libitum intake. Lambs were fed from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
8
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 0 publications
7
8
1
Order By: Relevance
“…Gill et al [14] reported that fishmeal supplementation improved protein retention while levels of fat accretion declined or remained unchanged. Similar findings were observed in lambs [22]. Contrary to this, some studies have found little response when supplementing with fishmeal [30].…”
Section: Introductionsupporting
confidence: 76%
“…Gill et al [14] reported that fishmeal supplementation improved protein retention while levels of fat accretion declined or remained unchanged. Similar findings were observed in lambs [22]. Contrary to this, some studies have found little response when supplementing with fishmeal [30].…”
Section: Introductionsupporting
confidence: 76%
“…Although higher carcass lean yield was obtained with lambs showing lower ADG, their carcasses were penalized for inferior muscular development and lower grade. A similar relationship has previously been documented in lambs fed silage alone or supplemented with protein or concentrates (Petit and Castonguay 1994).…”
Section: Carcass Characteristicssupporting
confidence: 58%
“…Maize, sorghum and other grass silages supplemented with different protein sources (such as fish meal, concentrate and addition of nitrogen sources) increased growth rate of growing animals (Kim et al, 2000). Petit and Castonguay (1994) observed that the ADG was lower (P<0.01) for lambs fed sole silage than those fed the silage plus concentrate. Similar results were reported by Sartori et al (2004) with sunflower silage in sheep and Chauhan and Gupta (1992) in buffalo calves with oat silage.…”
Section: Results and Discussion Chemical Composition Of Feed Ingrediementioning
confidence: 86%